MgO–C refractories based on refractory recyclates and environmentally friendly binders - Till M.J. Stadtmüller; Enrico Storti; Nora Brachhold; Anna-Marie Lauermannová; Ondřej Jankovský; Thomas Schemmel; Jana Hubálková; Patrick Gehre; Christos G. Aneziris (Open Ceramics, 2023)
This study focused on the development of an environmentally friendly binder system based on lignin and collagen for uniaxial pressed MgO–C refractories as an alternative to commonly used resin or pitch binders. Additionally, recycled MgO–C refractories from steel plants were partially utilized as raw material, investigating their influence on the resulting physical and mechanical properties. The binder system showed reliable binding properties, although the recyclate-containing MgO–C exhibited higher porosity, slightly lower density, and lower strength compared to the reference batches without recyclates. However, antioxidants significantly improved the properties of the recyclate-containing MgO–C samples. Scanning electron microscopy analysis with energy-dispersive X-ray spectroscopy revealed the formation of whiskers, as well as oxidation and nitridation of aluminum particles. This research highlights the potential of environmentally friendly binders and the utilization of recycled materials in MgO–C refractories to mitigate their environmental impact and enhances the environmental performance of carbon containing refractory materials.